2020
DOI: 10.1038/s41385-019-0218-5
|View full text |Cite
|
Sign up to set email alerts
|

Generation of protective pneumococcal-specific nasal resident memory CD4+ T cells via parenteral immunization

Abstract: The generation of tissue-resident memory T cells (T RM ) is an essential aspect of immunity at mucosal surfaces, and it has been suggested that preferential generation of T RM is one of the principal advantages of mucosally administered vaccines. We have previously shown that antigen-specific, IL-17-producing CD4 + T cells can provide capsular antibody-independent protection against nasal carriage of Streptococcus pneumoniae; but whether pneumococcus-responsive T RM are localized within the nasal mucosa and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…In bacterial infection models of Streptococcus pneumoniae 108 , 109 , Bordetella pertussis 110 , Klebsiella pneumoniae 76 , and Mycobacterium tuberculosis 111 , 112 respiratory tract CD4 + Trm have been shown to contribute to bacterial clearance, typically via the production of the pro-inflammatory cytokines IL-17 and IFNγ. An interesting report by Shenoy et al 113 provides insight into how mouse CD4 + Trm improves bacterial clearance from the lung.…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 99%
“…In bacterial infection models of Streptococcus pneumoniae 108 , 109 , Bordetella pertussis 110 , Klebsiella pneumoniae 76 , and Mycobacterium tuberculosis 111 , 112 respiratory tract CD4 + Trm have been shown to contribute to bacterial clearance, typically via the production of the pro-inflammatory cytokines IL-17 and IFNγ. An interesting report by Shenoy et al 113 provides insight into how mouse CD4 + Trm improves bacterial clearance from the lung.…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 99%
“…It has been hypothesized that Trm may be the most effective form of T cell response against SARS-CoV-2 infection 31 , capable of preventing viral dissemination beyond the URT, where more virus-induced damage can occur 32 . Data from mice have suggested that parenteral vaccination induces nasal Th17 Trm that protect against bacterial colonization 33,34 . However, our study is the first, to our knowledge, to suggest nasal T cells may be induced by parenteral vaccination against COVID-19.…”
Section: Main Textmentioning
confidence: 99%
“…Compared with their protective role in infectious diseases ( Wu et al, 2018 ; Wilk and Mills, 2018 ; Muruganandah et al, 2018 ; O’Hara et al, 2020 ), the importance and significance of T RM in tumor immunity are not adequately characterized. Nevertheless, recent studies in cancer-bearing mouse models have indicated a pivotal role of T RM in antitumor immunity in several tumor types ( Nizard et al, 2017 ; Milner et al, 2017 ; Malik et al, 2017 ; Enamorado et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%